« Laudato si’», une responsabilité cosmique de la maison commune - Philippe Crabbé (VertigO)
Laudato si’ is a long document, which adopts essentially the environmentalists’ traditional position including inter-discipinarity. Its author supports without reservation sustainable development, climate actions based on the precautionary principle and on the principle of common but differentiated responsibility that he considers as moral obligations. As an encyclical letter is foremost a religious and an ethical document, the former requires us to change our relations amongst ourselves and with nature, from domination – domination it qualifies as sin, which, therefore, affects our relations with God Trinity– to fraternity relations. Nature is personified in the fashion of Saint Francis of Assisi, patron saint of ecology. This is one of the reasons why the pope calls his encyclical, social rather than environmental. The latter reminds us of the priority to be granted to the poorest among us, to whom it assimilates to-day’s nature. The encyclical constitutes a vigorous attack against capitalism, its utilitarian ethics and its priority granted to technological progress and consumerism, which both reduce our freedom according to it. The pope thinks that the ecological crisis has a solution which lies in an ecological conversion on the model of the Trinity through education, both spiritual and cultural, and at the same time, individual and community-oriented. One must abandon consumerism for sobriety, the culture of domination over other individuals and over nature to the benefit of fraternity with both. With the encyclical, ecology from peripheral becomes central to the Christian message. Laudato si’ is not a great text but rather a great act of leadership.